Mirosław Mejzner SAC, L’escatologia di Metodio di Olimpo, Studia Ephemeridis „Augustinianum” 124, Roma 2011, Institutum Patristicum „Augustinianum”, ss. 381. - Misiarczyk, Leszek (Vox Patrum, 2011)
nie dotyczy